Effectiveness of two different campaigning methods in reaching the public: conventional pamphlet campaign versus social media campaign: a pilot study - E., Sharmila; V., Ramesh; R., Jayaprakash; S., Karthika; P., Shankar; D., Philomine Princy (International Journal Of Community Medicine And Public Health, 2023)
Cost effective campaigning method to attract people to an awareness program need to be identified. Conventional pamphlet campaign remain popular despite the expanding range of social media campaign that have potential to reach large number of people at low cost. Two different methods of awareness campaigns were used to attract people to an awareness program. The conventional pamphlet was distributed manually and social media campaign was done in Facebook as a paid promoted post. The budget was fixed to Rs.1200/-for each group. People with interest are invited to scan the provided QR code which directs to an electronic form (e-form). The number of sign up were estimated in each method. A total of 17 people signed up to participate in awareness program. Of which conventional pamphlets campaign showed 6 sign up and social media campaign showed 11 sign-ups. The cost per sign up for conventional pamphlet campaign and social media campaign are Rs.109.09 and Rs.200 respectively. The social media campaign was the cost-effective method and reached larger number of sign-ups when compared to conventional pamphlet campaign. Overall, our results demonstrate that social media campaigning is the cost-effective method in attracting people than conventional pamphlets campaigning.